Physiotherapy Extension Activities to Reduce Complaints of Low Back Pain in the Elderly Community at the Lawang Community Health Center: Penyuluhan Fisioterapi Untuk Mengurangi Keluhan Low Back Pain Pada Komunitas Lansia Di Puskesmas Lawang - David Satrya Wibowo; Siti Ainun Ma'rufa; Kusuma Hati (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
When someone reaches the age of 35 years and over, a person will usually start to experience complaints of lower back pain or also known as low back pain. As you get older, complaints of low back pain will increase. This counseling aims to provide education to the elderly community at the Lawang Community Health Center, Malang Regency, about exercises to reduce pain in the lower back. The method used is health promotion in the form of providing leaflets, training and education. The counseling went well and was easy for participants to understand so that in the evaluation results there was an increase in participants' knowledge from 0% to 100%. The target of activities to increase public knowledge has been achieved, and it is hoped that it can prevent pain in elderly people who have not been affected.